An inquiry into the judicial processes of spiritual damage compensation in Iran’s legal system - حمید ابهری/ مهدی طالقان غفاری * / مهرداد باکزاد/ الیاس یاری ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
Spiritual damage has been obviously stated to be parallel with material damage in the legal principle 171 of the Constitution of Islamic Republic of Iran, the articles 8, 9,and 10 of the 1339 Civil Liability Act, and the first and second notes of the article 14 of the 1392 Criminal Justice Act. In spite of the existence of strict laws in this regard, law courts have mostly taken notice of material damages at the expense of spiritual ones. As a result, there is a paucity of rich legal doctrines and judicialprocesses regarding spiritual damages inIran’s legal system. While a group of jurists believe in the impossibility ofcompensating spiritual damages, some others assert that spiritual damages are legally compensable. This study hence investigates the issue of spiritual damage and the viewpoints of its proponents and opponents in Iran’s Jurisprudence and legal system to unravel whether it is compensable or not. The study further aims to explore the possible methods of spiritual damage compensation.DOI /10.54633/2333-021-042-018